Optimization of conditions of agro-bacterial transformation of cotton pollen of Kazakhstan selection (Experimental biology, 2010)
Optimization of agrobacterial pollen transformation method for  cotton variety Kazakhstan selection has been carried out by the use of reporter GUS- and selective marker nptII- genes.  Transgenic plants of Maktaaral 4005 with  nptII- и GUS-  genes  have been obtained.